Bond Slip Study Between Concrete and Steel Interface Using Splice Beam Specimen Exposed to Elevated Temperatures. (October 2020) - Ahmad, Mohammad Suhaib; Bhargava, Pradeep
Abstract: Bond stress-slip behavior between the reinforcing steel and the concrete is one of the basic properties which influences the performance of the structure at the serviceability as well as at the ultimate limit state. However, this behavior changes with the exposure to elevated temperatures. Bond slip behavior after exposure to elevated temperatures have been studied using pull out specimens because of its ease of operation and economy. These specimens do not simulate the actual state of bond stress in reinforced concrete structures during testing. Therefore, an experimental study was conducted to investigate the effect of elevated temperatures on the bond behavior between reinforcing steel and concrete using splice beam specimen. The specimens were heated to three temperatures of 350 °C, 550 °C and 750 °C inside the furnace at a rate of 5 °C/min till the desired temperatures are achieved. The specimens were tested under four point bending to obtain i) relative slip between steel and concrete, ii) strain in the reinforcing bar and iii) mid span deflection of the beam specimens. The results show that the bond stress between reinforcing steel and concrete decreases after the exposure to elevated temperature while there relative slip increases. The reduction in bond stress is significant after the exposure to 550 °C. The reduction in the bond strength at a temperature is directly proportional to the reduction of its compressive strength at that temperature. A shift in the failure mode was observed in the beam specimens from a more brittle to a gradual failure after the exposure to 550 °C. Prediction of the bond strength for the beam specimens after elevated temperatures were also made using elastic, plastic and elastoplastic analysis based on thick wall cylinder theory. The analysis shows that the prediction based on plastic analysis overestimates the bond strength at elevated temperatures while the elastic and elastoplastic analysis shows conservative results. Based on the analysis, a model is proposed, which can predict the bond strength of splice beam specimens after exposure to elevated temperatures with considerably good efficiency.